Durability of the Therapeutic Effect of Restorative Neurostimulation for Refractory Chronic Low Back Pain. Issue 6 (9th July 2021) - Mitchell, Bruce; Deckers, Kristiaan; De Smedt, Kris; Russo, Marc; Georgius, Peter; Green, Matthew; Gulve, Ashish; van Buyten, Jean‐Pierre; Smet, Iris; Mehta, Vivek; Baranidharan, Ganesan; Rathmell, James; et al.
Abstract: Objectives: The purpose of the ongoing follow‐up of ReActiv8‐A clinical trial is to document the longitudinal benefits of episodic stimulation of the dorsal ramus medial branch and consequent contraction of the lumbar multifidus in patients with refractory mechanical chronic low back pain (CLBP). We report the four‐year outcomes of this trial. Materials and Methods: ReActiv8‐A is a prospective, single‐arm trial performed at nine sites in the United Kingdom, Belgium, and Australia. Eligible patients had disabling CLBP (low back pain Numeric Rating Scale [NRS] ≥6; Oswestry Disability Index [ODI] ≥25), no indications for spine surgery or spinal cord stimulation, and failed conventional management including at least physical therapy and medications for low back pain. Fourteen days postimplantation, stimulation parameters were programmed to elicit strong, smooth contractions of the multifidus, and participants were given instructions to activate the device for 30‐min stimulation‐sessions twice daily. Annual follow‐up through four years included collection of NRS, ODI, and European Quality of Life Score on Five Dimensions (EQ‐5D). Background on mechanisms, trial design, and one‐year outcomes were previously described. Results: At baseline ( N = 53) (mean ± SD) age was 44 ± 10 years; duration of back pain was 14 ± 11 years, NRS was 6.8 ± 0.8, ODI 44.9 ± 10.1, and EQ‐5D 0.434 ± 0.185. Mean improvements from baseline were statistically significant ( p < 0.001) and clinically meaningful for all follow‐ups. Patients completing year 4 follow‐up, reported mean (±standard error of the mean) NRS: 3.2 ± 0.4, ODI: 23.0 ± 3.2, and EQ‐5D: 0.721 ± 0.035. Moreover, 73% of participants had a clinically meaningful improvement of ≥2 points on NRS, 76% of ≥10 points on ODI, and 62.5% had a clinically meaningful improvement in both NRS and ODI and 97% were (very) satisfied with treatment. Conclusions: In participants with disabling intractable CLBP who receive long‐term restorative neurostimulation, treatment satisfaction remains high and improvements in pain, disability, and quality‐of‐life are clinically meaningful and durable through four years.